Determinants of STI's and contraceptive awareness among Indian adolescents: a hospital based study - Nidhi Gupta; Neha Varun; Arifa Anwar; Aruna Nigam (Barpeta Obstetrics and Gynaecological Society, 2021)
Objective: This study was done to assess the awareness of various contraceptive methods and sexually transmitted diseases among the adolescent females. Methods: It is a prospective observational study done in outpatient department of Obstetrics & Gynecology Department of Hamdard Institute of Medical Sciences & Research over a period of one year. All the unmarried and married adolescent females with age 11- 19 years who came to the hospital with any complaints were asked about their awareness regarding various methods of contraception and sexually transmitted diseases with the help of a pre-designed questionnaire. Results: Among these 216 participants, 69% were unmarried and 30% were married. Among unmarried, knowledge of contraception was present in 57.6% as compare to 72.3% among married participants. In our study, barrier method of contraception was the most acknowledged method followed by emergency contraceptive pills. Among all participants who were having knowledge of STI's (sexually transmitted infection), HIV is the only STI known. Conclusion: Safe sexual practices should be encouraged to avoid long term health and social disadvantages.